(untitled) (Research, Society and Development, 2022)
The assessment of the quality of water for human consumption is essential in preventing the health of the population. Due to the lack of public policies aimed at water treatment, monitoring is of great importance to obtain informative data on the quality of the water consumed, aiming at potability standards, especially in collective supply systems, such as schools. In this way, the work aimed to verify, through physical-chemical and microbiological analysis, the quality of the water of the wells that supply the reservoirs and the water stored in the drinking fountains of five schools in the municipality of Capanema-PA, in addition to verifying if these are in accordance with the potability standards established by the Ministry of Health. A total of 123 water samples were carried out, 60 from the wells, 60 from the drinking fountains and 03 from the taps. It was possible to observe that the water was considered unsatisfactory due to different factors, which could be due to the presence of pathogenic organisms (fecal coliforms and Escherichia coli), turbidity and/or pH outside the standards established in the legislation. Due to the unsatisfactory microbiological results obtained, in some schools, simplified chloradpores were implanted for water treatment. The results obtained reveal that the physical-chemical and microbiological parameters present the need for corrective actions at all stages of the supply of water for human consumption, through the hygiene conditions taken by those responsible for supplying the school and also by monitoring and controlling the quality. of water by the health authorities.